Integrating connectionless and connection-oriented traffic using quantum packets - Lam, R.; Chan, H.; Dillon, Tharam S.; Li, V.; Leung, V. (Elsevier Science, 2005)
Recently, integrating connectionless (CL) and connection-oriented (CO) traffic has been of considerable interest. While CO traffic is often transferred by asynchronous transfer mode (ATM), it is preferable to use multiprotocol label switching (MPLS) for CL traffic. To packetize CL and CO traffic flexibly and efficiently, we propose a general packetization mechanism, the ‘quantum packet’ method. In view of the increasing need to integrate CL and CO traffic, we use a Markov model to analyze the packet loss ratio and the average packet transfer delay when these two types of traffic are integrated under three multiplexing schemes. The results provide us with a better understanding of the behavior of the system, as well as valuable insights into the development of integrated networks.